Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/sj.bjc.6600467
|View full text |Cite
|
Sign up to set email alerts
|

A ‘modified de Gramont’ regimen of fluorouracil, alone and with oxaliplatin, for advanced colorectal cancer

Abstract: The standard de Gramont (dG) regimen of fortnightly leucovorin, bolus fluorouracil and 22-h infusion of fluorouracil, d1+2, and the same regimen plus oxaliplatin, are effective but also cumbersome. We therefore present simplified 'Modified de Gramont' (MdG) regimens. Forty-six advanced gastrointestinal cancer patients entered a dose-exploring study of MdG, including an expanded cohort of colorectal cancer patients at optimum dose. Treatment (fortnightly) comprised: 2-h i.v.i. leucovorin (350 mg d,l-LV or 175 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 17 publications
(15 reference statements)
3
91
1
Order By: Relevance
“…In a phase II study in relapsed patients, FOLFOX7 produced a response rate of 42% and grade 3/4 neurological toxicity of 15% (Maindrault-Goebel et al, 2001). A subsequent study showed that a modified 5-FU schedule combined with 85 mg m À2 but with reductions of both oxaliplatin and 5-FU for haematologic toxicity once again reducing the oxaliplatin dose, was associated with marked reduction in efficacy in the second line setting -12% in 37 patients but with a remarkable 72% response rate in 25 first-line patients (Cheeseman et al, 2002). The discrepancy remains unexplained, but still suggests that the need for enhanced dose intensity of oxaliplatin above 85 mg m À2 requires exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II study in relapsed patients, FOLFOX7 produced a response rate of 42% and grade 3/4 neurological toxicity of 15% (Maindrault-Goebel et al, 2001). A subsequent study showed that a modified 5-FU schedule combined with 85 mg m À2 but with reductions of both oxaliplatin and 5-FU for haematologic toxicity once again reducing the oxaliplatin dose, was associated with marked reduction in efficacy in the second line setting -12% in 37 patients but with a remarkable 72% response rate in 25 first-line patients (Cheeseman et al, 2002). The discrepancy remains unexplained, but still suggests that the need for enhanced dose intensity of oxaliplatin above 85 mg m À2 requires exploration.…”
Section: Discussionmentioning
confidence: 99%
“…That trial included 24 assessable patients who received the regimen as first-line therapy for metastatic colorectal cancer, whose case-notes and scans were reviewed by an independent external radiologist and oncologist; 72% had RECIST complete or partial responses, confirmed by a second scan; a further 8% had partial responses that were not confirmed by a second scan (Cheeseman et al, 2002). That high response rate (72% confirmed; 80% confirmed þ unconfirmed) was markedly higher than, although statistically consistent with, other first-line trials of FU/FA with oxaliplatin (De Gramont et al, 2000;Tournigand et al, 2001;Goldberg et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In our single centre study, this new regimen demonstrated exceptional activity as first-line treatment, and was also well tolerated and convenient (Cheeseman et al, 2002). We now present data from a prospective multicentre phase 2 study of a further 55 patients receiving the same OxMdG schedule as first-line treatment for advanced colorectal cancer.…”
mentioning
confidence: 83%
“…fluorouracil and bevacizumab. Six oxaliplatin-and two irinotecanbased chemotherapy regimens were allowed (Tables 1 and 2) [3][4][5][6][7][8][9][10]. Patients randomized to the panitumumab treat-ment arm received 6 mg/kg every 2 weeks by i.v.…”
Section: Methodsmentioning
confidence: 99%